1995
DOI: 10.1016/0042-6989(94)00125-6
|View full text |Cite
|
Sign up to set email alerts
|

Interocular suppression in the primary visual cortex: a possible neural basis of binocular rivalry

Abstract: In an attempt to demonstrate a physiological basis for the alternating suppression of perception when the two eyes view very different contours (binocular rivalry), we studied the responses of neurons in the lateral geniculate nucleus (LGN) and area 17 of cats for drifting gratings of different orientation, spatial frequency and contrast in the two eyes. Almost half of the LGN neurons studied exhibited modest inhibitory interocular interaction, but independent of interocular differences in orientation. Monocul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
112
1
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(123 citation statements)
references
References 53 publications
(77 reference statements)
9
112
1
1
Order By: Relevance
“…Decades ago, binocular rivalry was considered by many to be a bottom-up driven visual phenomenon whose dynamics were determined primarily by the interplay of adaptation and inhibition within early visual cortex (Levelt, 1965;Matsuoka, 1984;Mueller, 1990;Lehky & Blake, 1991;Sengpiel et al, 1995). But that view began to change as evidence mounted for the involvement influences originating beyond early visual cortex, influences including attentional modulation of dominance at the onset of rivalry (Mitchell et al, 2004) and interocular grouping in the formation of global, coherent dominance during rivalry (e.g., Kovács et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Decades ago, binocular rivalry was considered by many to be a bottom-up driven visual phenomenon whose dynamics were determined primarily by the interplay of adaptation and inhibition within early visual cortex (Levelt, 1965;Matsuoka, 1984;Mueller, 1990;Lehky & Blake, 1991;Sengpiel et al, 1995). But that view began to change as evidence mounted for the involvement influences originating beyond early visual cortex, influences including attentional modulation of dominance at the onset of rivalry (Mitchell et al, 2004) and interocular grouping in the formation of global, coherent dominance during rivalry (e.g., Kovács et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…One view is that rivalry is image-based rather than eye-based (Kovacs et al, 1996;Logothetis et al, 1996), though recent work has found that whatever the drive, the consequences can be observed as early as the LGN (Haynes et al, 2005;Wunderlich et al, 2005). Notwithstanding the involvement of higher-order interactions Logothetis et al, 1996;Logothetis, 1998;Macknik and Martinez-Conde, 2004;Tse et al, 2005), it now seems likely that a substantial contribution to binocular rivalry arises from interocular suppression (Sengpiel et al, 1995;Harrad, 1996;Wilson, 2003;Lee and Blake, 2004;Freeman et al, 2005). Nevertheless, it has been difficult to determine the origins of the effects observed in various brain areas within either functional or anatomical maps (Polonsky et al, 2000;Haynes et al, 2005;Lee et al, 2005;Tse et al, 2005;Wunderlich et al, 2005).…”
Section: Binocular Rivalrymentioning
confidence: 99%
“…The stimuli used in studies of XOS are similar to those frequently used in studies of another, presumably related form of suppression (Sengpiel et al, 1995;Harrad, 1996;Brown et al, 1999) known as binocular rivalry. In a typical experiment, very different images (e.g.…”
Section: Binocular Rivalrymentioning
confidence: 99%
See 1 more Smart Citation
“…Contralateral dominance might thus be based on suppression properties at early neural sites in the visual pathway (Sengpiel & Blakemore, 1994;Sengpiel, Blakemore, & Harrad, 1995). The dominance of ipsilateral view, on the other hand, may indicate the influence of sustained attention to a stimulus in the primed eye through the binocular correspondence stage (Ooi & He, 1999).…”
Section: Discussionmentioning
confidence: 99%